Falco peregrinus Tunstall 1771 ... - Bishop, K. David (Zenodo, 2023)
*PEREGRINE FALCON Falco peregrinus Range F. p. calidus and F. p. ernesti Biak, Yapen. Status Palearctic winter visitor (F. p. calidus) and rare visitor (F. p. ernesti). There are few records of resident ernesti and even fewer of the Palearctic migrant calidus anywhere in New Guinea (Beehler & Pratt 2016; KDB & SvB). 5 April 2006: Dutson (2006) saw one of the small resident subspecies in flight at dusk; June 2008: a member of a bird tour group saw one in southern Biak but without details (van Beirs 2008); February 2011: two F. p. calidus (Germi et al. 2013). 13 January 1994: P. Gregory (in litt. 2000) saw an adult with a rather pale grey mantle, perched in a dead tree on Owi, which was clearly not resident ernesti but presumably one of the Palearctic migrant subspecies. ... : Published as part of Bishop, K. David, 2023, The avifauna of Biak Island, Papua, Indonesia with comments on status, conservation, natural history and taxonomy, pp. 3-62 in Bulletin of the British Ornithologists' Club 143 (1) on page 41, DOI: 10.25226/bboc.v143i1.2023.a2, http://zenodo.org/record/11642130 ...